Pendidikan Lingkungan Hidup Untuk Meningkatkan Ecoliteracy Siswa - Yossita Wisman; Joko Santoso (FKIP Universitas Palangka Raya, 2024)
As time goes by, the population is increasing. With the increasing population, it causes environmental problems. Environmental problems occur due to the greed of humans to exploit nature. Humans are no longer thinking about the impacts of their exploitation. Along with the occurrence of these problems, environmental education was held in schools. The aim is that with this environmental education it is hoped that students will understand more about how their environment is, about what impacts will occur if they overexploit nature. The purpose of this study was to find out how environmental education increases ecoliteracy. The method in this research is library research (library research). The result is that environmental education in schools can increase students' ecoliteracy competence.